FDI and income inequality: Evidence from Europe - Dierk Herzer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2011)
This paper examines the relationship between foreign direct investment (FDI) and income inequality for a sample of ten European countries over the period 1980 to 2000. Using panel co-integration and causality techniques that are robust to omitted variables, slope heterogeneity, and endogenous regressors, we find that: (1) FDI has a positive short-run effect on income inequality in Europe, (2) the long-run effect of FDI on inequality, however, is negative on average, (3) long-run causality runs in both directions, suggesting that an increase in FDI reduces income inequality and, in turn, higher inequality leads to lower FDI inflows, and (4) there are large differences in the long-run effect of FDI on income inequality, with two countries (Ireland and Spain) exhibiting a positive relationship between FDI and income inequality.
Keywords: F21; D31; C23; 330; FDI; income inequality; panel co-integration; Europe; Direktinvestition; Ausländisch; Verteilungswirkung; Einkommensverteilung; Europa